The group-based lifestyle-integrated functional exercise intervention for older adults: theory- and evidence based intervention development and evaluation from a health behavior change perspective - Labudek, Sarah (2022)
The promotion of healthy aging becomes increasingly important against the background of a growing aging population around the world. The aging process is associated with a loss of physical function and an increased prevalence of falls, which can be effectively prevented by multi-component physical activity such as balance and strength training. However, older adults rarely meet the recommended amount of physical activity or oftentimes withdraw shortly after engagement in interventions. The Lifestyle-integrated Functional Exercise (LiFE) intervention provides an innovative, habit-based approach to fall prevention and physical activity promotion in older adults by linking functional balance and strength activities to daily routines. This dissertation project is embed-ded in the LiFE-is-LiFE trial, a randomized non-inferiority trial with the aim to make LiFE suit-able for large-scale implementation by developing and testing a group-based LiFE (gLiFE) format. The aims of the presented work are to enrich the LiFE-is-LiFE project and differentiate it from the health behavior change perspective. gLiFE was developed and evaluated alongside the MRC guidelines for the development and evaluation of complex interventions with a focus on psychological determinants of behavior change. In the development process of gLiFE, empir-ically established health psychological theories such as the health action process approach (HAPA), the self-determination theory, and habit formation theory as well as the behavior change technique (BCT) taxonomy were applied. To better understand how gLiFE promotes physical activity and prevents falls, gLiFE was evaluated in comparison to LiFE with regard to multiple outcomes, such as effectiveness (e.g., activity-adjusted falls), the participants’ per-ceptions, and changes in psychological determinants of health behavior change (e.g., motiva-tional and volitional constructs or habit strength). Community-dwelling older adults aged 70 years and older at risk of falling were eligible for participation in the LiFE-is-LiFE trial. LiFE and gLiFE were both delivered in seven intervention sessions over the course of 11 weeks, followed by two booster phone calls. The baseline sample comprised N = 309 individuals who were 78.8 (range 70-94) years old on average, with the majority of participants being female (73.5%). Follow-up assessments took place 6 and 12 months after intervention start. This dissertation project includes six publications which are based on data from the LiFE-is-LiFE trial. The first publication was preparatory research to examine the relationship between theory-based psychological determinants derived from the HAPA and self-determination the-ory with older adults’ sensor-measured daily walking duration as a specific marker for physi-cal function. Findings indicate that intrinsic motivation, but not HAPA-based social-cognitive determinants were related to older adults’ walking duration. The second publication presented the conceptual gLiFE framework and its initial feasibility testing. My contribution was the modification and extension of the original conceptual LiFE model regarding behavior change theory. The development process resulted in a gLiFE train-er’s manual. The results of the initial feasibility testing suggest that gLiFE is feasible, accepted by the target group, and is associated with positive changes in psychological determinants of behavior change such as action and coping planning or habit strength. In the third publication, the evaluation of LiFE and gLiFE from the participants’ perspective was reported with a focus on acceptability. Results of qualitative analyses based on focus group interviews with a subsample of participants (n = 30) who completed the 6-month follow-up suggest that participants accept gLiFE and LiFE equally. Regarding behavior change, LiFE and gLiFE participants reported successful habit formation. The latter three publications were based on data from the full sample assessed at 6- and 12-month follow-up. In the fourth publication, the new gLiFE intervention underwent a non-inferiority testing regarding activity-adjusted falls, which revealed inconclusive results. Alt-hough gLiFE participants did not show a similar reduction of activity-adjusted falls as LiFE participants, they significantly increased their daily step count compared to LiFE participants. In the fifth publication, a quantitative evaluation of participants’ perspective on LiFE and gLiFE regarding general and more specific contents such as behavior change strategies like action planning was conducted using data from the 6- and 12-month follow-up. Overall, gLiFE par-ticipants rated the overall satisfaction, program-specific aspects, and perceived effectiveness as good and stable over time. Compared to the ratings of LiFE participants, only marginal differences arose, e.g., regarding the perceived helpfulness of planning. In the sixth and final publication, the changes in psychological determinants of behavior change (i.e., self-efficacy, outcome expectancies, risk perception, intention, action planning, coping planning, action control, habit strength, autonomy, competence, relatedness, and in-trinsic motivation) through LiFE and gLiFE were reported. Results showed that LiFE and gLiFE mainly induced long-term changes in volitional determinants such as action control. Both LiFE and gLiFE participants still showed above mid-scale levels of habit strength of the LiFE activities at 12-month follow-up. Taken together, the current work provides evidence for gLiFE to be a valuable theory-based fall prevention and physical activity promotion intervention for older adults aged 70 years and older. The discussion lays out similarities and differences between LiFE and gLiFE. My re-search suggests implications for research, referring to both the behavior change process and to the delivery of LiFE and gLiFE. Additionally, implications for gLiFE trainers and potential stakeholders are provided. The dissemination of gLiFE has already been initiated, paving the way for a larger number of older adults to be supported in aging healthily and actively.
Keywords: Hochschulschrift